A bibliometric analysis of traditional Chinese non-pharmacological therapies in the treatment of knee osteoarthritis from 2012 to 2022 - Zhang, Shouyao; Wang, Yuanwang; Zhou, Meng; Jia, Shan; Liu, Ye; Zhang, Xinghe; Tai, Xiantao (Frontiers in Neuroscience, 2023)
Objective: Knee osteoarthritis (KOA) is a serious musculoskeletal disease, and the benefits of traditional Chinese non-pharmacological therapy in the treatment of KOA are receiving increasing attention. Through systematically analyze the global research on traditional Chinese non-pharmacological therapy in KOA from 2012 to 2022 in the form of a knowledge map to truly comprehend worldwide involvement, research hotspots and future trends in this field. Methods: Literature related to traditional Chinese non-pharmacological therapy used in the treatment of KOA from 2012 to 2022 was searched from the Web of Science core database and PubMed database. CiteSpace, SCImago Graphica and VOSviewer were used to extract relevant countries, institutions, authors, journals, references, keywords, as well as the most widely used acupoints, intervention methods and evaluation indexes for the final objective assessment. Results: A total of 375 articles have been included. The total number of publications has shown a fluctuating growth over the last decade. A total of 252 articles were published in China. The most productive institutions and authors were from China, represented by Cun-Zhi Liu and Jian-Feng Tu from the Beijing University of TCM. Osteoarthritis Cartilage was the most frequently cited journal, and the most frequently cited literature was "OARSI guidelines for the non-surgical management of knee, hip, and poly articular osteoarthritis". "Acupuncture", "complementary therapy"were hot keywords. The prevalence of KOA was high in middle-aged women. ST36 (Zusanli), ST10 (Dubi), and GB34 (Yanglingquan) were the most frequently used acupoints, while manual acupuncture, electro-acupuncture, and moxibustion were the most concerned traditional Chinese non-pharmacological therapy, and WOMAC, VAS, SF-36 were the most widely used evaluation indexes. Conclusion: A large body of evidence supports the potential application of traditional Chinese non-pharmacological therapy in KOA rehabilitation. The advantages for KOA have attracted researchers to explore this field. Relieving pain, reducing functional impairment and improving quality of life in KOA patients are common goals of researchers, with middle-aged and elderly women being the focus group. At present, the development of traditional Chinese non-pharmacological therapy is uneven, and the current evidence is limited, more high-quality randomized controlled trials(RCT) are needed to confirm the long-term impact on KOA.